Fiscal decentralization and efficiency of public services delivery by local governments in Ghana - Isaac Otoo; Michael Danquah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
In this paper, we estimate the efficiency of Metropolitan, Municipal, and District Assemblies (MMDAs) in Ghana, and investigate the impact of fiscal decentralization on the efficiency of local public goods and services delivery by MMDAs. Using data from composite budgets of all 216 MMDAs, we employ both nonparametric and parametric frontier methods to carry out the study. The results with regard to our two indicators of fiscal decentralization indicate that fiscal autonomy proxied by MMDAs' internally generated funds as a share of their total revenue has a positive influence on the efficiency of MMDAs whilst vertical imbalance-a high share of central government grants in MMDAs' total expenditure-does not improve the delivery of local goods and services by MMDAs in Ghana. The findings indicate a clear signal to policy managers to prioritize support to MMDAs in the mobilization of internally generated revenue.
Keywords: H71; H72; H75; H77; 330; fiscal decentralization; efficiency; local government; frontier methods; Ghana